Effect of micro-osteoperforation on the rate of canine retraction: a split-mouth randomized controlled trial - Amira A. Aboalnaga; Mona M. Salah Fayed; Noha A. El-Ashmawi; Sanaa A. Soliman (SpringerOpen, 2019)
Abstract Background Among the recent modalities introduced to accelerate orthodontic tooth movement (OTM) is micro-osteoperforations (MOPs), in other words, bone puncturing. The aim of this split-mouth trial was to investigate the effects of MOPs on the rate of OTM. Methods Eighteen patients requiring bilateral first premolar extraction and upper canine retraction with maximum anchorage were enrolled in this study. Immediately before canine retraction, three MOPs were randomly allocated to either the right or left sides. MOPs were performed using a mini-screw (1.8 mm diameter, 8 mm length) distal to the canine. Canine retraction continued for 4 months. Data were collected from monthly digital models, in addition to pre- and post-retraction maxillary CBCT images. The primary outcomes were the rate of canine retraction per month and the total distance moved by the canines. The secondary outcomes were the effect of MOPs on anchorage loss, canine root resorption, and pain. Results The mean rate of canine retraction in both sides was 0.99 ± 0.3 mm/month. The total distance moved by the canine cusp tip was greater in the MOP than the control side (mean difference 0.06 ± 0.7 mm), which was statistically insignificant (P > 0.05(. The total distances moved by the canine center and apex were significantly greater in the MOP than the control side (mean difference 0.37 ± 0.63 mm (P < 0.05) and 0.47 ± 0.56 mm (P < 0.01) respectively). Insignificant differences were detected regarding anchorage loss and root resorption between both sides (P > 0.05). Mild to moderate pain was experienced following the MOP procedure, which rapidly faded away within 1 week. Conclusions Micro-osteoperforations were not able to accelerate the rate of canine retraction; however, it seemed to facilitate root movement.